2016
DOI: 10.1021/acs.orglett.6b02271
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-Bond-Promoted Double Radical Isocyanide Insertion under Visible-Light Irradiation: Synthesis of 2-Fluoroalkylated Quinoxalines

Abstract: A halogen-bond-promoted double radical isocyanide insertion with perfluoroalkyl iodides is reported. With perfluoroalkyl iodides as halogen-bond donors and organic bases as halogen-bond acceptors, fluoroalkyl radicals can be generated by a visible-light-induced single electron transfer (SET) process. The fluoroalkyl radicals are trapped by o-diisocyanoarenes to give quinoxaline derivatives. This mechanistically novel strategy allows the construction of 2-fluoroalkylated 3-iodoquinoxalines in high yields under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(81 citation statements)
references
References 48 publications
4
76
0
1
Order By: Relevance
“…A complex between a nitrogen base and R F -I has very recently been postulated to generate R F radicals upon visible light irradiation. [18][19][20] We have also observed the same trends for the formation of a complex TMEDA$2C 4 F 9 I based on NMR data ( 19 F, 13 C NMR), where spectral changes are observed when going from free reagents to the complexed mixture, as indicated in Table S1. † The 19 F NMR upeld shis observed in the I-CF 2 -C 3 F 7 are…”
supporting
confidence: 53%
“…A complex between a nitrogen base and R F -I has very recently been postulated to generate R F radicals upon visible light irradiation. [18][19][20] We have also observed the same trends for the formation of a complex TMEDA$2C 4 F 9 I based on NMR data ( 19 F, 13 C NMR), where spectral changes are observed when going from free reagents to the complexed mixture, as indicated in Table S1. † The 19 F NMR upeld shis observed in the I-CF 2 -C 3 F 7 are…”
supporting
confidence: 53%
“…Ma, Yu and colleagues have reported a halogen‐bond‐promoted double radical isocyanide insertion with R F –I in the presence of organic bases (Bn 2 NH). The scope of the transformation is depicted in Scheme .…”
Section: Visible Light Photoactive Eda Complexes Involving Rf–i Anmentioning
confidence: 99%
“…Based on the above experimental observation and previous reports by Yu and others, we propose a plausible mechanism for the photoinduced vicinal difluoroalkylation and aminosulfonylation of alkynes, which is shown in Scheme . We reason that initially, DABCO⋅(SO 2 ) 2 combines with 2 to generate a halogen‐bonding (XB) adduct A . This XB adduct is reduced by Mes‐Acr + red to form a difluoroalkyl radical in the presence of visible light.…”
Section: Methodsmentioning
confidence: 52%
“…This result suggests that the reaction proceeds through a radical process. Recently, Yu and co‐workers reported a halogen‐bond‐promoted double‐radical isocyanide insertion with perfluoroalkyl iodides . They demonstrated that fluoroalkyl radicals could be obtained through single‐electron transfer (SET) under visible light.…”
Section: Methodsmentioning
confidence: 99%